CRIMINAL-LEGAL CHARACTERISTICS AND FEATURES OF THE SPREAD OF SEXUALLY TRANSMITTED DISEASES OR HIV / AIDS - Муродов Акмал Баходирович (Modern American Journals, 2025)
The article reveals the concept, legal characteristics, public danger, elements of a crime related to the spread of sexually transmitted diseases or HIV (AIDS). The legal framework for counteracting the detection of crimes, the subjects intended for counteraction and some aspects that should be implemented by them were also considered.
Keywords: Venereal disease, HIV infection, AIDS, social risk, crime against health, crime against the psyche, emergency prevention measures.